ISOLASI DAN IDENTIFIKASI SENYAWA AKTIF LARVASIDA DARI BIJI MIMBA (Azadirachta indika A. Juss) TERHADAP LARVA NYAMUK DEMAM BERDARAH (Aedes aegypti) - I W. Suirta; N. M Puspawati; N. K. Gumiati (Jurnal Kimia (Journal of Chemistry), 2007)
Isolation and identification of larvicidal active compounds towards Aedes aegypti from Mimba seed havebeen conducted. One kilogram dry powder of Mimba seed was extracted with ethanol at room temperature.Evaporation of ethanol gave 30 g of crude ethanol extract which showed activity against Aedes aegypti (LC50282.29). This extract was dissolved into methanol-water (7:3) and was then partitioned with n-hexane, chloroformand ethyl acetate respectively. The three extracts obtained i.e. n-hexane, chloroform and ethyl acetate were showedtheir activity against Aedes aegypti in which the-n-hexane extract was the most active with LC50 of 143.97.Therefore the n-hexane extract was further purified using silica gel column chromatography with chloroform:nhexane(9:1) as eluent. Three fractions was obtained i.e. F1, F2 and F3 and they were all active against Aedes aegyptiwith LC50 78.45, LC50 113.54 and LC50 58.70 respectively. It can be seen that F3 was the most active fractions butfrom TLC result, F1 showed the relatively pure compounds since it only gave one spot. Therefore F1 was furtheridentified using pyhtochemical testing, Uv-Vis, infrared and GC-MS. It was found that the larvicidal activecompounds F1 was belong to carboxylic acids groups,with l max 290.1 having functional groups such as methyl,methylene and carbonil. Identification using GC-MS indicated that the larvicidal active compounds F1 was assumedto be a combination of 7 compounds derived from carboxylic acids including hexa-decanoic acid, etil-hexadecanoate,oleic acid, etyl-oleate ester, octadecanoic acid, etyl-octadecanoate and dioctyl-hexadioate.